2009
DOI: 10.1016/j.applthermaleng.2008.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Heating characteristics of convection reflow ovens

Abstract: Abstract:The inhomogeneous temperature distribution in the reflow oven can cause soldering failures. In this project, we investigate how the construction of a convection reflow oven has an affect on its heating characteristics. In the convection reflow oven itself, the heating capability is mainly dependent on the heat transfer coefficient, which in turn is mostly determined by the gas flow parameters. Therefore, we study how the construction of the reflow oven affects the flow of gas in the oven. Our conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Illés and Harsányi (2009a, 2009b) reported that the heating capability of reflow ovens was affected by the oven’s construction. First, they studied the gas flow circumstances in the reflow oven using a stationary and isothermal gas flow model.…”
Section: Challenges In Modelling the Reflow Soldering Processmentioning
confidence: 99%
“…Illés and Harsányi (2009a, 2009b) reported that the heating capability of reflow ovens was affected by the oven’s construction. First, they studied the gas flow circumstances in the reflow oven using a stationary and isothermal gas flow model.…”
Section: Challenges In Modelling the Reflow Soldering Processmentioning
confidence: 99%
“…To start the process of reflow soldering, with the basic principle of soldering in saturated vapours, the stabilization of temperature and saturation of vapour inside the oven is a basic requirement (Géczy et al, 2013). For that matter, investigations are widespread in this topic, (Ankrom et al, 1989;Plotog et al, 2010aPlotog et al, , 2010bGéczy et al, 2013), with a general use of thermocouple-based temperature detection on the Printed Circuit Boards (PCBs) and inside the workspace as well (Livovsky and Pietrikova, 2017;Illés and Harsányi, 2009). Temperature detection is also important on PCB level.…”
Section: Introductionmentioning
confidence: 99%
“…For that matter, investigations are widespread in this topic, (Ankrom et al 1989), , (Géczy et al 2013), with a general use of thermocouple based temperature detection on the PCB-s and inside the workspace as well (Livovsky and Pietrikova, 2017) (Illés and Harsányi, 2009). Temperature detection is also important on PCB level.…”
mentioning
confidence: 99%
“…Vapour Phase Soldering (VPS) is a reflow soldering method, which is more complex from the aspect of heat transfer than conventional convection- [1,2,3], or IR heating [4] based reflow processes.…”
Section: Introductionmentioning
confidence: 99%